ENGLISH TEACHERS’ PERCEPTIONS AND IMPLEMENTATION OF PEDAGOGICAL CONTENT KNOWLEDGE IN TEACHING ENGLISH TO YOUNG LEARNERS - Virgianti, Ni Made Sukreni; Purnamika Utami, I G A Lokita; Dewi, Kadek Sintya (Universitas Pendidikan Ganesha, 2020)
This study aimed at investigating primary English teachers’ perceptions and implementation of Pedagogical Content Knowledge in teaching English to young learners, and the consistency between the teachers’ perceptions and implementation of PCK in teaching English to young learners. This study involved three English teachers from three different primary schools in Buleleng regency which were selected by using Convenience sampling technique. The research design was embedded QUAL-quan mixed method. The instruments used to collect the data were questionnaire, observation sheet, and interview guide. The data were analyzed by using descriptive qualitative. The study demonstrated that teachers had high perceptions of PCK. However, their PCK implementation was very low. Thus, there is no consistency between the perceptions and implementation of PCK. Moreover, based on the result of the interview, the teachers encountered some problems included difficulty in using English in speaking and writing, designing learning activities to facilitate students’ characteristics, choosing media that related to the material, and providing learning media due to lack of facility in the school. Therefore, schools administrators need to promote English teachers’ improvement of pedagogical content knowledge by proposing them to participate in the certain professional development program.